Acute and chronic finger injuries in ball sports - Abarca, Javier; Almusa, Emad; Al-Qattan, Mohammad M.; Arrowsmith, Jill; Atlan, Frank; Chick, Grégoire 1963- (France : Springer, 2013)
Neglected finger injuries may lead to chronic lesions that often have detrimental consequences for the practice of a ball sport, whether at a recreational level or at the top athlete level. The initial injury management is crucial. Depending on the type and the severity of the lesions, different people may get involved: the players themselves or their entourage, physiotherapists, club doctors, emergency physicians, family doctors, sports doctors or hand surgeons. Treatment is usually conservative: the long fingers require rapid mobilization to prevent stiffness and contrary to that, the thumb requires stability. Surgery may be necessary to reach these goals especially for athletes, because of the demands of their sport. Chronic lesions are also in part related to repeated trauma, requiring specialized long-term multidisciplinary treatment. They can often lead to the end of a sporting career, but also may limit the functionality of the fingers at the time of conversion.
La función de los autores fue determinada por el catalogador
Keywords: DEDOS -- HERIDAS, LESIONES, ETC; DEDOS -- CIRUGIA; LESIONES DEPORTIVAS; ACCIDENTES DEPORTIVOS; MEDICINA DEPORTIVA